Vercingetorix in the series of L. Hostilio Saserna (RRC 448)? - Amela Valverde, Luis (Documenta & Instrumenta - Documenta et Instrumenta, 2022)
It is common to see that various studies and investigations and coin auction houses allude to the representation of the Arverni chief Vercingetorix in a Roman denarius minted by L. Hostilio Saserna. This paper studies this monetary series and its relationship with the conquest of Gaul carried out by C. Julius Caesar.
Keywords: Vercingétirux; L. Hostilio Saserna; C. Julius Caesar; Gallic Wars; Second Roman Civil War